2021
DOI: 10.18052/www.scipress.com/jhpr.14.1
|View full text |Cite
|
Sign up to set email alerts
|

Chilling-Requirement Release of Seed and Bud Dormancy in Apricot

Abstract: Dormancy shows common physiological features in buds and seeds. Specific period of chilling is usually required to release dormancy. Reproductive meristems and embryos display dormancy mechanisms in specialized structures named respectively buds and seeds that arrest the growth of perennial plants until environmental conditions are optimal for survival. Chilling requirements for breaking dormancy were studied for 3 successive years in 20 seedling apricot trees which spanned the range of flowering times in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…[12]. El-Yazal (2020) conducted a study on the low-temperature conditions of breaking dormancy for 20 apricot seedlings for three consecutive years and found that cold stratification at 5 • C had the best effect on breaking seed dormancy and germination [19]. Heide and Prestrud (2005) studied the growth and dormancy of four apple cultivars and one pear cultivar and found that at least 6 weeks (about 1000 h) of chilling at 6 or 9 • C were required for the release of dormancy and recovery of growth, while chilling at 12 • C for 14 weeks treatment is almost ineffective [10].…”
Section: Discussionmentioning
confidence: 99%
“…[12]. El-Yazal (2020) conducted a study on the low-temperature conditions of breaking dormancy for 20 apricot seedlings for three consecutive years and found that cold stratification at 5 • C had the best effect on breaking seed dormancy and germination [19]. Heide and Prestrud (2005) studied the growth and dormancy of four apple cultivars and one pear cultivar and found that at least 6 weeks (about 1000 h) of chilling at 6 or 9 • C were required for the release of dormancy and recovery of growth, while chilling at 12 • C for 14 weeks treatment is almost ineffective [10].…”
Section: Discussionmentioning
confidence: 99%